2014
DOI: 10.3389/fncel.2014.00147
|View full text |Cite
|
Sign up to set email alerts
|

The ER mitochondria calcium cycle and ER stress response as therapeutic targets in amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease characterized by progressive loss of upper and lower motor neurons. Although the etiology remains unclear, disturbances in calcium homoeostasis and protein folding are essential features of neurodegeneration in this disorder. Here, we review recent research findings on the interaction between endoplasmic reticulum (ER) and mitochondria, and its effect on calcium signaling and oxidative stress. We further provide insights into studies, providing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 210 publications
(236 reference statements)
2
70
0
3
Order By: Relevance
“…The endoplasmic reticulum (ER) stress response and increased levels of oxidative stress are associated with the expression of mutant TDP-43 or FUS proteins in cells 24 . Thus, we investigated whether nlp-29::GFP expression was induced by either ER or oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…The endoplasmic reticulum (ER) stress response and increased levels of oxidative stress are associated with the expression of mutant TDP-43 or FUS proteins in cells 24 . Thus, we investigated whether nlp-29::GFP expression was induced by either ER or oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…SOD1, the first identified ALS gene, has been extensively studied with regard to its role in the pathogenesis of this condition with the use of transgenic mice expressing various ALS-linked mutants of human SOD1 (Vinsant et al 2013). Such studies have revealed various mitochondrial abnormalities in these mice, including impairment of ATP permeation through the mitochondrial outer membrane, membrane hyperpolarization, and disturbance of mitochondrial Ca 2+ flow, which is functionally connected to Ca 2+ signaling in the endoplasmic reticulum (Tadic et al 2014;Tan et al 2014) (Fig. 2j).…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…S1R is a receptor with chaperone-like activity in the endoplasmic reticulum and regulates Ca 2+ release from this organelle into mitochondria (Hayashi and Su 2007). It has also been implicated in other acute and chronic neurodegenerative disorders (Tadic et al 2014). Intriguingly, a defect in the selective uptake of Ca 2+ into mitochondria has been identified in the end-stage of ALS in SOD1(G93A) transgenic mice (Fuchs et al 2013).…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…In fact, mitochondria are located where high amounts of ATP are required (34) and also where Ca 2 + signaling needs tight regulation (126). Importantly, alterations in mitochondrial Ca 2 + have been related to several pathologies, including neurodegenerative diseases such as amyotrophic lateral sclerosis (ALS) (318), and aging (332). In recent years, it has been demonstrated that mitochondria actively interact with ER membranes through structuredenominated mitochondria-associated membranes, which enable direct and rapid exchange of lipids and Ca 2 + between the two compartments.…”
mentioning
confidence: 99%